DNA methylation and gene expression profiles characterize epigenetic regulation of lncRNAs in colon adenocarcinoma. Issue 3 (6th November 2019) - Li, Zhijin; Tan, Hua; Yu, Hai; Deng, Zhong; Zhou, Xiaobo; Wang, Maode
Abstract: The long noncoding RNAs (lncRNAs) are associated with tumorigenesis and progression of cancer. While DNA methylation is a common epigenetic regulator of gene expression, the methylation of lncRNAs was rarely studied. To address this gap, we integrated DNA methylation and RNA‐seq data to characterize the landscape of lncRNA methylation in colon adenocarcinoma (COAD). We collected and analyzed the lncRNA expression and methylation data from The Cancer Genome Atlas and Cancer Cell Line Encyclopedia to identify the epigenetically regulated lncRNAs. We further investigated the biological and clinical relevance of the identified lncRNAs via bioinformatics analysis. We identified 20 epigenetically upregulated lncRNAs in COAD, including several well‐studied lncRNAs whose methylation regulation were poorly investigated, such as PVT1 and UCA1. We also revealed several novel tumor‐associated lncRNAs in COAD, including GATA2‐As1 and CYTOR. Next, we explored their biology function using gene set enrichment analysis and competitive endogenous RNA analysis. We characterized the methylation landscape of lncRNA in COAD and identified 20 epigenetically upregulated lncRNAs. Our findings will shed new light on the epigenetic regulation of lncRNA expression by DNA methylation. Abstract : We identified 20 epigenetically upregulated lncRNAs in COAD. PVT1 expression is negatively correlated with the methylation in the promoter, GATA2‐As1 expression is positively correlated with the methylation in the gene body. Upregulated CYTOR is associated with poor survival and could be acting as competitive endogenous RNA.